METHODS AND TECHNIQUES USED DURING THE DEVELOPING COMMUNICATIVE SKILLS - Zokirova Zulfiya Tursunovna (American Journals Publishing, 2023)
The article presents studies on the implementation ways of communicative language teaching activities in the classroom. The article is given the topicality, aim, and practical significance of the chosen theme. It is fully proved the importance of communicative language teaching activities in teaching language. The actuality of this work is the investigation of some innovative communicative language teaching activities in the way of development of speaking skills to provide communication in learning a foreign language and making ESP classrooms more effective teaching environments as a facilitator.
Keywords: communicative language teaching, individual work, organization, investigation, effective teaching, innovative communicative language.